Acoustics target tracking - Neo, Xin Ai. (2010)
As the project title suggests, acoustic target tracking, is to locate the digital information transmitted through a highly scattering medium using the Time Reversal Signal Processing (TRSP). TRSP can be used for many purposes such as: medical personnel could use it for imaging and therapy without destroying the good cells, unlike chemotherapy. Military also uses it for battlefield communications without having their transmission intercepted. However, TRSP is still a new technology and has many undeveloped and undiscovered aspects. Therefore, this project’s aim is to uncover these facets with the help of the simulation tools, MATLAB, and also to improve the current techniques. A new method based on iterations of time reversal process (ITRSP) is also presented in this project. This report will explain how the ITRSP appears to be more efficient and how it achieves the inverse filter of propagation in the subspace of non-null singular values of the time reversal operator with respect to the TRSP. Lastly, the report will present the influence of external noise and shows the number of iterations that will give the lowest error rate based on researches.